2013
DOI: 10.7196/sajs.1220
|View full text |Cite
|
Sign up to set email alerts
|

Firearm injuries to children in Cape Town, South Africa: Impact of the 2004 Firearms Control Act

Abstract: Compared with the earlier study, this study showed a significant reduction in the number of children presenting with a firearm-related injury. Mortality and inpatient stay were also significantly reduced. The study shows the impact that the Firearms Control Act has had in terms of paediatric firearm-related injury and provides evidence that the medical profession can play an important role in reducing violence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 9 publications
(13 reference statements)
0
17
1
Order By: Relevance
“…Of major concern was their finding that 94 patients with GSWs were admitted to hospital, but three times as many died before admission and were taken straight to mortuaries, showing the heavy burden of gunshot injuries to children. In the Western Cape Province at Red Cross War Memorial Children's Hospital, Campbell et al [11] found the same incidence as Mars and Hadley but with a ten-fold increase in prehospital compared with in-hospital deaths. Although the Firearms Control Act of 2004 appeared to have an impact, the effect appears to be waning with a steady increase in incidence in the latter part of their study.…”
Section: Fig 2 Frequency (%) Of Body Regions Injured According To Imentioning
confidence: 75%
See 3 more Smart Citations
“…Of major concern was their finding that 94 patients with GSWs were admitted to hospital, but three times as many died before admission and were taken straight to mortuaries, showing the heavy burden of gunshot injuries to children. In the Western Cape Province at Red Cross War Memorial Children's Hospital, Campbell et al [11] found the same incidence as Mars and Hadley but with a ten-fold increase in prehospital compared with in-hospital deaths. Although the Firearms Control Act of 2004 appeared to have an impact, the effect appears to be waning with a steady increase in incidence in the latter part of their study.…”
Section: Fig 2 Frequency (%) Of Body Regions Injured According To Imentioning
confidence: 75%
“…Tragically, similar findings have been reported from other SA studies over the past two decades. [10,11] In KZN, Mars and Hadley [10] reported the peak incidence of GSWs in children to occur in the first quintile of life, multisystem injuries were the commonest presentation, and of those who survived, one in ten was left severely disabled. Of major concern was their finding that 94 patients with GSWs were admitted to hospital, but three times as many died before admission and were taken straight to mortuaries, showing the heavy burden of gunshot injuries to children.…”
Section: Fig 2 Frequency (%) Of Body Regions Injured According To Imentioning
confidence: 99%
See 2 more Smart Citations
“…Most children admitted with firearm-related injuries are victims of 'stray bullets' . [5] Causes of child abuse and predisposing factors…”
Section: Physical Violence Against Childrenmentioning
confidence: 99%